Penetapan Harga Akad Murabahah pada BMT Putra Arta Syariah - Aspika, Riqi B1031131070 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ASTRACT This research aims to determine the suitability of the implementation of regulating murabahah, announcement regulating murabahah price and also to indicate the marriage al-'inah located on such as BMT Putra Arta Shari'a. This research using descriptive qualitative approach by interviewing board such and such managers. The results of this research is that such as BMT Putra Arta Syariah not apply regulating murabahah that corresponds with fatwas DSN MUI. Regulating murabahah price assignment using proportional method with modifications on the options pencicilan and not that there is an indication that such as BMT Putra Arta Shari'a practicing marriage al-'inah on marriage murabahah. Key Words : Murabahah, the assignment price, Regulating al-'inah